CSU-CHILL polarimetric radar measurements from a severe hail storm in eastern Colorado - Hubbert, J., author; Carey, L. D., author; Bringi, V. N., author; Bolen, S., author; American Meteorological Society, publisher (Colorado State University. Libraries, 1998)
Polarimetric radar measurements made by the recently upgraded CSU-CHILL radar system in a severe hailstorm are analyzed permitting for the first time the combined use of Zh, ZDR, linear depolarization ratio (LDR), KDP, andρhv to infer hydrometeor types. A chase van equipped for manual collection of hail, and instrumented with a rain gauge, intercepted the storm core for 50 min. The period of golfball-sized hail is easily distinguished by high LDR (greater than or equal to 218 dB), negative ZDR (less than or equal to 20.5 dB), and low ρhv (less than or equal to 0.93) values near the surface. Rainfall accumulation over the entire event (about 40 mm) estimated using KDP is in excellent agreement with the rain gauge measurement. Limited dual-Doppler synthesis using the CSU-CHILL and Denver WSR-88D radars permit estimates of the horizontal convergence at altitudes less than 3 km above ground level (AGL) at 1747 and 1812 mountain daylight time (MDT). Locations of peak horizontal convergence at these times are centered on well-defined positive ZDR columns. Vertical sections of multiparameter radar data at 1812 MDT are interpreted in terms of hydrometeor type. In particular, an enhanced LDR "cap" area on top of the the positive ZDR column is interpreted as a region of mixed phase with large drops mixed with partially frozen and frozen hydrometeors. A positive KDP column on the western fringe of the main updraft is inferred to be the result of drops (1-2 mm) shed by wet hailstones. Swaths of large hail at the surface (inferred from LDR signatures) and positive ZDR at 3.5 km AGL suggest that potential frozen drop embryos are favorably located for growth into large hailstones. Thin section analysis of a sample of the large hailstones shows that 30%-40% have frozen drop embryos.